DEVELOPMENT AND EVALUATION OF A STRATEGY FOR MACEDONIAN ENERGY TRANSITION - Gligor Kanevce, Aleksandar Dedinec and Aleksandra Dedinec (My University, 2021)
This paper analyzes the possibility of energy transition in Macedonia within the framework of the energy development strategy up to 2040. Namely, a detailed review of the current state of the Macedonian energy system is provided. Additionally, the analysis takes into account the early effect of COVID-19 on the consumption in the energy system, which is reflected on the projections of the macroeconomic parameters and energy demand in different sectors. Global trends, as well as policies and measures at European level were taken into account while planning the development of the energy system, with a special attention to the Energy Community guidance. For that purpose, three scenarios were defined: reference, moderate transition and green scenario. A methodology which integrates two modeling tools MARKAL and EnergyPLAN was developed. In that regard, the pathways presented in this paper follow good EU practices of renewable energy sources and energy efficiency policies, as well as decarbonisation, taking into consideration targets and trajectories with realistic dynamics that are adjusted to domestic specifics and priorities. The results show reduction of energy consumption, and GHG emissions while increasing GDP and increasing the share of renewable energy sources, which will enable the import dependence not to increase from the 2019 level. These results can be achieved at a cost of the energy system which is lower compared to the price in a scenario in which there are smaller investments in energy efficiency and RES.
Keywords: Energy transition, Macedonia, Renewable energy sources, power plants